Large-scale volcanism and the heat death of terrestrial worlds - Way, M. J. (The Planetary science journal)
Large-scale volcanism has played a critical role in the long-term habitability of Earth. Contrary to widely held belief, volcanism, rather than impactors, has had the greatest influence on and bears most of the responsibility for large-scale mass extinction events throughout Earth’s history. We examine the timing of large igneous provinces (LIPs) throughout Earth’s history to estimate the likelihood of nearly simultaneous events that could drive a planet into an extreme moist or runaway greenhouse, leading to the end of volatile cycling and causing the heat death of formerly temperate terrestrial worlds. In one approach, we make a conservative estimate of the rate at which sets of near-simultaneous LIPs (pairs, triplets, and quartets) occur in a random history statistically the same as Earth’s. We find that LIPs closer in time than 0.1–1 million yr are likely; significantly, this is less than the time over which terrestrial LIP environmental effects are known to persist. In another approach, we assess the cumulative effects with simulated time series consisting of randomly occurring LIP events with realistic time profiles. Both approaches support the conjecture that environmental impacts of LIPs, while narrowly avoiding grave effects on the climate history of Earth, could have been responsible for the heat death of our sister world Venus.